2014
DOI: 10.2494/photopolymer.27.307
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Mobility in Organic Thin-film Transistors: Limiting Factors and Countermeasures

Abstract: Device physics in organic thin-film transistors (OTFTs) have been extensively studied along with the efforts to improve device performance and to develop their applications. Among many promising organic semiconducting materials, pentacene has been a benchmark in this research field. Understanding the bottlenecks of carrier transport in pentacene OTFTs is therefore important to maximize the performance of OTFTs. In this paper, we summarize our knowledge on the bottlenecks against carrier transport in practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Figure 5 shows possible mechanism of conduction model. For smaller gate voltage, the drain current was proportional to the drain voltage [4], as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Figure 5 shows possible mechanism of conduction model. For smaller gate voltage, the drain current was proportional to the drain voltage [4], as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 89%
“…Temperature dependence of V D -I D characteristics can be explained with two possible charge transport mechanisms which are Schottky thermionic emission and polycrystalline model at ground boundary. [4] In the forward applied voltage V D region, temperature dependence of V D -I D characteristics can be fitted by the Schottky thermal emission mechanism model with barrier height range from 33 to 57 meV, as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that the charge transport could be explained using a polycrystalline model in a pentacene thin-film transistor. 31) The activation energy of C6-DNT-V (between 33 and 73 meV) originated from the Schottky thermal emission between C6-DNT-V and the MoO 3 =Au electrode, where the typical mobility was 1.1 cm 2 V −1 s −1 with a C6-DNT-V thickness of 40 nm. The mobility decreased to 0.48 cm 2 V −1 s −1 when using only the Au electrode, and the process condition for C6-DNT-V was not changed.…”
Section: Resultsmentioning
confidence: 99%
“…Pentacene is a p-type benchmark material that has been largely studied in the field of organic electronics with relatively better hole mobilities greater than 1 cm 2 /V.s in the thin-film form [49,50]. Thus, with the combined advantages of thin-film grown pentacene and Schottky configuration, in the present work we have fabricated pentacene based photodiode to detect x-rays directly.…”
Section: Jinst 17 P02024mentioning
confidence: 99%